Efficacy of Open Learning System on College of Education Students’ Achievement in Woodwork Technology - Oladiran Stephen Olabiyi (Indonesian Journal of Educational Research and Technology, 2024)
The study explored the effectiveness of open learning as one of the educational approaches to equip youths for job market/self-employment, thereby increasing their self-reliance and combating the ever-increasing poverty problem. The efficacy of open learning for teaching woodwork design and construction in Nigerian colleges of education was determined using a pre-test, post-test non-equivalent control quasi-experimental design. Three null hypotheses and three research questions guided the study in which the experimental group was taught woodwork design and construction using an open learning system while the control group received instruction with the conventional teaching method for ten weeks. Wood Design and Construction Achievement Test (WDCAT) comprised of drawing and practical tests with a KR-21 reliability coefficient of 0.88 employed for data collection. Results showed that students in the experimental group achieved significantly better performance in woodwork design and construction than students in the control group. Although no significant difference existed between genders taught wood design and construction using an open learning system. Based on the findings, it was recommended that an open learning system should be encouraged in teaching woodwork design and construction in Nigerian educational institutions.